2019
DOI: 10.1002/adom.201900258
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Vacancies in Bi2S3yielding Sub‐Bandgap Photoresponse and Highly Sensitive Short‐Wave Infrared Photodetectors

Abstract: Defects play an important role in tailoring the optoelectronic properties of materials. Supported by density functional theory (DFT) calculations, herein it is demonstrated that sulphur vacancies are able to engineer sub‐band gap photoresponse in the short‐wave infrared range due to formation of in‐gap states in Bi2S3 single crystals. Sulfurization and subsequent refill of the vacancies result in faster response but limit the spectral range to the near infrared as determined by the bandgap of Bi2S3. A facile c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…The calculated elemental ratio (Bi/S: 39.85/60.15) is in good agreement with the stoichiometry of Bi 2 S 3 , which confirms the formation of stoichiometric Bi 2 S 3 . 67 Different chalcogenide metal-ligand precursors can be mixed to make solid solutions of Group V metals (Bi 1Àx Sb x ) 2 S 3 (0 r x r 0.05), via the so-called ''composition engineering''. The well-defined XRD patterns shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated elemental ratio (Bi/S: 39.85/60.15) is in good agreement with the stoichiometry of Bi 2 S 3 , which confirms the formation of stoichiometric Bi 2 S 3 . 67 Different chalcogenide metal-ligand precursors can be mixed to make solid solutions of Group V metals (Bi 1Àx Sb x ) 2 S 3 (0 r x r 0.05), via the so-called ''composition engineering''. The well-defined XRD patterns shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks in Figure 3 corresponds to uncoordinated Bi, thereby confirming the existence of sulfur vacancies in the 150 films. 36,37,38 The atomic ratio of Bi to S was calculated from the areas of Bi 4f7/2 and S 2p3/2 and the results are summarized in Figure 3 The electrical conductivity of the vacuum annealed samples was measured, and the room temperature values are plotted in Figure 3(c). We concluded that 300 °C was the minimum vacuum annealing temperature necessary to introduce S vacancies that contributed to the total carrier concentration in this system and that 400 °C is the upper boundary in the temperature scale for operation, since the films become mechanically unstable with all sulfur removed according to the XPS analysis [see Supporting Information, Figures S7(c) and (d)].…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 , 24 , 25 , 26 , 27 ] Furthermore, sulfurization can reduce trap density of states of the Bi 2 S 3 and lower 1/ f noise. [ 28 ]…”
Section: Introductionmentioning
confidence: 99%